Implementasi Program Kerja Kampus Mengajar Dalam Penggunaan Aplikasi Canva Untuk Meningkatkan Kemampuan Adaptasi Teknologi Peserta Didik Di SMP Satu Atap 1 Lembar - Ulfa, Mariam; Puspita, Dewa Ayu Dwik Dela; Azzahra, Siti Masyitah; Gunada, I Wayan; Dewi, Putu Nita Nugraha; Sani, Safira Ziaratul; Sulitiawan, Andri (Universitas Mataram, 2024)
The campus teaching program is one of the programs organized by the Ministry of Education and Culture which provides opportunities for all students throughout Indonesia to teach in junior high schools, one of which is One Roof 1 Sheet Middle School which is located in West Lombok district, NTB province. One of the goals of the Class 6 campus teaching program is to help schools adapt to technology. The activity methods used are material presentation, practice, mentoring and evaluation. The result of this program is that students have broader knowledge regarding the Canva application.